Relações entre percepção auditiva e orientação e mobilidade em um grupo de pessoas com deficiência visual usuárias de cão guia - Castro, Oliveiros Barone (2019)
INTRODUCTION: People with low vision or blind, need to use some resource that allows them to walk around the city in a safer way, the cane being the best known and used option for mobility, as it serves to identify obstacles that are front or ground level; the so-called low obstacles. When the cane is used, using the technique known as sweeping, the user moves it from side to side drawing an arc on its own front, but must touch the obstacle to identify it and only then deviate from it. Another option is the guide dog properly trained so that the user and dog can be a team. From the innumerable abilities acquired in their training, the guide dog anticipates and deflects the user's route before reaching the low obstacles, as well as the medium and aerial obstacles, avoiding the user to hit anything and thus avoid injuries to the body and / or head, providing greater security and agility in the process of displacement and mobility of blind or low vision people. For people to be able to use these resources, they must know and properly apply specific techniques to walk around better, it’s called Orientation and Mobility, and as they have lost vision functionality, they must resort to the remaining senses. In this direction, hearing is fundamental in this process, since it is the sense that will provide several possibilities of reference and location in the most varied environments. OBJECTIVE: Describe mobility and orientation relationship and auditory perception in visually impaired users of guide dogs. METHOD: Qualitative study , 09 people with visual impairment (blind and with low vision) have participated, being 08 with acquired loss vision and 01 with congenital visual impairment, 02 female and 07 male, between the ages of 23.0 and 64.0 years, dog guide users for at least 1 year. It was applied - 1. Questionnaire of personal characterization. 2. Functional technical assessment of Guidance and Mobility. 3. Audiological assessments. RESULTS: Nine (09) audiological evaluations were completed. The audiometric curve of eight (08) people was within normal limits bilaterally and in the remaining one the audiometric curve of the sensorineural type presented normal degree and descending configuration accentuated bilaterally, suggesting presbycusis. Results of all the tests applied are within the standard of normality and all participants presented high level of auditory abilities. CONCLUSION:Comparative evaluation between what was verified in the audiological tests and what was observed in the functional evaluation of orientation and mobility, points the need of some adaptions in OM technique , as well as technical adequacy of the team training that users received. It was verified that hearing /auditory perception are not related to the points raised in the technical evaluation. It is worth mentioning that when evaluating the temporal resolution for consecutive sound stimuli by RGDT, it was possible to observe that in this group of blind people, the threshold value ranged from 3.5 to 7.5 msec. It is interesting to note that these values are lower than those commonly found in the adult hearing population